Demographic Factors as Predictors of Open Educational Resources Awareness and Usage among Open and Distance Learning Students in Southwestern Nigeria (2019)
This study assessed the joint and relative contributions of demographic factors (age, sex, marital status, school, and academic level) to the prediction of Open Educational Resources awareness and usage among open and distance learning students in Southwestern Nigeria. The study adopted a descriptive research design of the survey type. Three ODL institutions (University of Ibadan Distance Learning Centre, University of Lagos Distance Learning Institute, and the National Open University of Nigeria, Ibadan Study Centre) were purposively selected. A structured questionnaire titled "OER awareness and usage Questionnaire" was pilot-tested, and an Alpha coefficient of .95 was obtained. Data collected from the study were analyzed using frequency count, simple percentages, and multiple regression analysis. Results of the study revealed that there is a joint contribution of age, sex, marital status, school, and academic level to the prediction of OER awareness and usage. It was further revealed that while school, academic level, and age had a significant relative contribution to the prediction of OER awareness among the students, sex and marital status had no significant relative contribution. Also, sex, marital status, and school have a significant relative contribution to OER usage, but age and academic level of students had no contribution. It was therefore concluded that if all these demographic factors are properly considered in the drive towards increasing OER awareness and usage among ODL students, there is a greater chance that high feet could be achieved both in terms of awareness and usage of open educational resources among the students in order to boost the academic performance and in turn improve productivity level of ODL institutions in the country